According the data analyse to study of the Frost Resistance of Corrugated Metal Pipe Culverts in Permafrost Regions. Issue 1 (1st February 2023) - Wang, Xu; Yu, Tianlai
Abstract: In this paper, we mainly studied the stress variation law of corrugated pipe culvert in permafrost regions under the influence of external load and temperature field, and formulated the corresponding experimental arrangement and observation scheme, in order to reveal the mechanical characteristics and action mechanism of corrugated metal pipe culverts.At the same time, we studied the law of the upper limit variation of permafrost foundation under corrugated pipe culvert, established the finite element model of corrugated pipe culverts, and for which we conducted mechanical analysis, frost heave analysis, and solution(thawing) settlement analysis; measured the variation of earth pressure and temperature field around pipe wall during and after filling soil.